Retraction Statement: Copper‐Catalyzed Synthesis of Substituted Isoindolo[2, 1‐a]quinoxalines and Isoindolo[2, 1‐a]quinoxalin‐6(5H)‐ones. Issue 36 (30th November 2016) - Biswas, Subhasish; Batra, Sanjay
Abstract: The following article from the European Journal of Organic Chemistry, published online on June 17, 2013 in Wiley Online Library (onlinelibrary.wiley.com, doi: 10.1002/ejoc.201300466) and in print ( Eur. J. Org. Chem .2013, 4895–4902), has been retracted by agreement between the corresponding author, the journal Editor, Dr. Haymo Ross, and Wiley‐VCH Verlag GmbH & Co. KGaA. The retraction has been agreed to for the following reasons. The synthesis described in this manuscript uses the products from a previous Advanced Synthesis and Catalysis article ( Adv. Synth. Catal .2011, 353, 3330−3334) as precursors. As discovered by Professor Jérôme Thibonnet and co‐workers, Université François Rabelais, Tours, the products of this previous paper are not isoindoles but the corresponding indoles. Therefore, the structures of the newly synthesized derivatives are also incorrect.